Effect of bioslurry and chemical fertilizer on the agronomic performances of maize - Tsehay Kebede; Yadessa Gonfa Keneni; Abate Feyissa Senbeta; Getachew Sime (Heliyon, 2023)
The objective of this study was to determine the effects of bioslurry (BS) and chemical fertilizer (CF), as a sole BS and CF and their mixed application, on the agronomic performances of maize (Zea mays var. BH- 546). Field experiment was conducted at Hawassa University Research Farm, in the Sidama Region in Ethiopia. The experiment consisted of six treatments, arranged in a randomized complete block design with three replications. Relevant agronomic characteristics were recorded for each plot, from planting to harvest. Results show yield and yield characteristics of maize increased by both sole and combined application of fertilizers compared to no fertilizer application. The combined BS and CF application at the dose of 25% BS +75% CF gave the highest plant height (251.3 cm), grain yield (7.09 t ha−1), biomass yield (24.4 t ha−1) and stover yield (11.5 t ha−1). The agronomic performances generally increased with increasing proportion of chemical fertilizer in the combined application until the proportion of bio-slurry reaches 75%. Moreover, the combined application generally tended to increase the agronomic performance better than the sole application of both BS and CF. In addition to improving the agronomic performances; both sole BS and its combination with CF reduce the cost of chemical fertilizers. In conclusion, the combined BS and CF application at the dose of 25% BS +75% CF appears an optimal combination and rate for the production of maize in the study area. Yet, as this finding is only one season, further studies determining the optimum dose of sole BS, sole CF, and combined CF and BS for improved maize agronomic performance is commendable in future research.